The Effect of Content Duration and Subtitles of TikTok Live Social Media Marketing on Word of Mouth Online Halal Fashion Products - Alam, Azhar; Bulan, Lita Cahya; Hakim, Lukmanul (International Review of Management and Marketing, 2025)
This study investigates the impact of content duration and subtitles in TikTok Live marketing on electronic word-of-mouth (eWOM) for halal fashion products. Utilizing a quantitative approach, we analyzed 161 videos from 49 TikTok accounts promoting halal fashion between October 1-14, 2023. The methodology included Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis via SmartPLS software. Findings indicate that longer video durations negatively affect eWOM (path coefficient - 0.368, P-value 0.022), while subtitles have a positive but statistically insignificant effect (path coefficient 0.453, P-value 0.058). User engagement metrics revealed high levels of “Likes” and “Saves,” but low comment rates, suggesting a passive consumption pattern. These results highlight the necessity for halal fashion marketers to focus on shorter videos with engaging visual elements to enhance user interaction and eWOM potential on TikTok. This research contributes to digital marketing literature by providing actionable insights for developing effective social media strategies tailored to the halal fashion sector in Indonesia, a rapidly growing market with significant opportunities for innovation and consumer engagement.